SELECTIVE IGA DEFICIENCY MIMICKING CHURG-STRAUSS SYNDROME AND HYPEREOSINOPHILIC SYNDROME: A CASE REPORT - TAKAHASHI, NORIYUKI (Nagoya J Med Sci, 2013)
Selective IgA deficiency (SIgAD) is the most common type of primary immunoglobulin deficiency. Most individuals with SIgAD are asymptomatic. However, some patients are associated with allergic and autoimmune disease. SIgAD is included in the list of differential diagnoses of eosinophilia. We experienced a patient who initially presented with abdominal pain and eosinophilia. A >1-year follow-up revealed SIgAD, and we had difficulty differentiating it from Churg-Strauss syndrome (CSS) or hypereosinophilic syndrome (HES). A 66-year-old Japanese male presented with a history of recurrent abdominal pain. A diagnostic work-up revealed eosinophilia, eosinophilic gastritis, eosinophilic pneumonia, and SIgAD over 1 year of clinical observation. He also suffered from asthma and sinusitis. Anti-neutrophil cytoplasmic antibody was negative and vasculitis was not detected in the obtained tissue specimens of stomach, lung, nose and skin. The patient showed no evidence of drug ingestion, parasitic infections, or malignant neoplasms. Although we cannot rule out prevasculitic CSS and idiopathic HES, the whole clinical picture in this patient can be explained most consistently by SIgAD.